GENDER PECULIARITIES OF THE SPECTRUM OF CHROMOSOMAL ABERRATIONS IN PERIPHERAL BLOOD LYMPHOCYTES OF HEALTHY PERSONS AND PATIENTS WITH GENERALIZED PERIODONTITIS - M. I. Khomyk; L. Ye. Kovalchuk; H. M. Melnychuk (Український стоматологічний альманах)
Introduction. Generalized periodontitis (GP) refers to the diseases with multifactorial heredity, in which the variability of one or another sign is determined not by one major gene, but by the influence of a large number of hereditary and external factors with small effects. An important component for the research of immuno-cytogenetic status of healthy persons and patients with multifactorial diseases is the study of chromosomal abnormalities. For this purpose, a method of metaphase analysis of karyotype in peripheral blood lymphocytes is used.